The Florentines : from Dante to Galileo : the transformation of Western civilization - Strathern, Paul, 1940- (Pegasus Books, 2021)
Examines the cultural transformation characterized by an increasing emphasis on humanism that emerged in the city of Florence between the birth of Dante in 1265 and the death of Galileo in 1642, and its role in the Renaissance.